A Short version of the revised 'experience of close relationships questionnaire': Investigating Non-clinical and clinical samples - Wongpakaran,T. (Bentham Science Publishers B.V., 2015)
Aim: This study seeks to investigate the psychometric properties of the short version of the revised 'Experience of Close Relationships' questionnaire, comparing non-clinical and clinical samples. Methods: In total 702 subjects participated in this study, of whom 531 were non-clinical participants and 171 were psychiatric patients. They completed the short version of the revised 'Experience of Close Relationships' questionnaire (ECR-R-18), the Perceived Stress Scale-10(PSS-10), the Rosenberg Self-Esteem Scale (RSES) and the UCLA Loneliness scale. A retest of the ECR-R-18 was then performed at four-week intervals. Then, confirmatory factor analyses were performed to test the validity of the new scale. Results: The ECR-R-18 showed a fair to good internal consistency (α 0.77 to 0.87) for both samples, and the test-retest reliability was found to be satisfactory (ICC = 0.75). The anxiety sub-scale demonstrated concurrent validity with PSS-10 and RSES, while the avoidance sub-scale showed concurrent validity with the UCLA Loneliness Scale. Confirmatory factor analysis using method factors yielded two factors with an acceptable model fit for both groups. An invariance test revealed that the ECR-R-18 when used on the clinical group differed from when used with the non-clinical group. Conclusions: The ECR-R-18 questionnaire revealed an overall better level of fit than the original 36 item questionnaire, indicating its suitability for use with a broader group of samples, including clinical samples. The reliability of the ECR-R18 might be increased if a modified scoring system is used and if our suggestions with regard to future studies are followed up. © Wongpakaran and Wongpakaran; Licensee Bentham Open.